Modified lithium-rich manganese-based material, preparation method thereof, positive plate and battery
By introducing dual -alkaline metal manganese -rich matrix in the lithium -rich manganese -based material and forming a three -phase composite structure of P2 layer -like phase and spinels, the problem of the performance and cost of traditional lithium -rich material materials has been solved, and it has achieved efficient and efficient and efficient and efficient and efficient. Stable electrochemical performance and low cost.
Patent Information
- Application Number
- CN202411886921.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Traditional lithium-rich manganese-based materials have problems such as low efficiency, poor rate performance, poor cycle stability and high cost for the first time, which limits their commercial applications.
By introducing a bi-alkali metal manganese-rich matrix and replacing part of Li+ with Na+, it is transformed into a unique P2 layered phase, and a spinel phase with a more stable structure is formed through the sodium-lithium exchange reaction, combined with appropriate amounts of M and D element doping , forming a three-phase composite structure of O3 lamellar phase-P2 lamellar phase-spinel phase.
It improves the first Coulombic efficiency, discharge capacity, rate performance and cycle stability of the material, while reducing the cost, making it suitable as a cathode material for secondary batteries.
Smart Images

Figure CN119361677A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a modified lithium-rich manganese-based material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C products, energy storage systems and power batteries due to their high energy density, long cycle life and good rate performance. How to further improve the energy density and cycle life of lithium-ion batteries has also become a research hotspot in the field of lithium-ion batteries. As the core part of lithium-ion batteries, positive electrode materials play a vital role in the preparation of high-performance lithium-ion batteries.
[0003] Currently, the commonly used positive electrode materials are lithium cobalt oxide (LiCoO2, LCO), nickel cobalt manganese ternary material (LiNi x Co y Mn 1-x- y O2, NCM), nickel-cobalt-aluminum ternary materials (LiNi x Co y Al 1-x-y O2, NCA), lithium iron phosphate (LiFePO4, LFP) and lithium manganese oxide (LiMn2O4, LMO). Among them, lithium-rich manganese-based materials (Li-rich NCM) have high manganese content and low nickel and cobalt content, and there are two charge compensation mechanisms for anions and cations. Compared with cobalt-based materials and nickel-based materials, they have higher specific capacity and lower cost. However, traditional lithium-rich manganese-based materials still have problems such as low first coulomb efficiency, poor rate performance, poor cycle stability and high cost, which limit the commercial application of lithium-rich manganese-based materials. Summary of the invention
[0004] Based on this, it is necessary to provide a modified lithium-rich manganese-based material and its preparation method, a positive electrode sheet and a battery to solve the problems of low first coulombic efficiency, poor rate performance, poor cycle stability and high cost existing in traditional lithium-rich manganese-based materials.
[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0006] In a first aspect of the present application, a modified lithium-rich manganese-based material is provided, comprising a double alkali metal manganese-rich matrix;
[0007] The double alkali metal manganese-rich matrix is expressed as: Li 1+x Na z Mn a Co b Ni c M 1-a-b-c O 2+x+z-y Dy ;
[0008] Among them, 0 <x<0.5,0<z<0.2,0≤y≤0.1;
[0009] 0.6≤a≤0.75, 0≤b≤0.1, 0.25≤c≤0.4, 0<1-abc≤0.05;
[0010] The M element includes one or more of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr;
[0011] The D element includes one or more of F, Cl and S;
[0012] The double alkali metal manganese-rich matrix comprises an O3 layered phase, a P2 layered phase and a spinel phase, and the total mass fraction of the P2 layered phase and the spinel phase in the double alkali metal manganese-rich matrix is 1% to 15%.
[0013] In one embodiment, the P2 layered phase is uniformly dispersed in the double alkali metal manganese-rich matrix and is in close contact with the O3 layered phase;
[0014] The distribution concentration of the spinel phase gradually decreases in the direction pointing inward along the surface of the double alkali metal manganese-rich matrix.
[0015] In one embodiment, the X-ray diffraction pattern of the double alkali metal manganese-rich matrix satisfies the following conditions:
[0016] (1) There is a (003) crystal plane diffraction peak at 2θ=18°~19°, which belongs to the O3 layered phase;
[0017] (2) There is a (104) crystal plane diffraction peak at 2θ = 43°~46°, which belongs to the O3 layered phase, and the left side of the (104) crystal plane diffraction peak has a shoulder peak or broadening belonging to the spinel phase;
[0018] (3) There is a diffraction peak at 2θ = 15.2°~16.2°, which belongs to the P2 layered phase;
[0019] (4) There is a superlattice diffraction peak at 2θ=20°~23°, which is attributed to Li2MnO3.
[0020] In one embodiment, the M element includes one or more of Nb, W, Mo, Sb, Cr and Zr.
[0021] In one embodiment, the modified lithium-rich manganese-based material also includes a coating layer loaded on the double alkali metal manganese-rich matrix, and the coating layer includes one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
[0022] In a second aspect of the present application, a method for preparing the modified lithium-rich manganese-based material as described above is provided, comprising the following steps:
[0023] A manganese-rich precursor, a lithium source, a sodium source and a dopant are mixed and subjected to a first sintering treatment to obtain a first intermediate;
[0024] Dispersing the first intermediate in a lithium salt solution for ion exchange treatment, and performing solid-liquid separation and drying treatment to obtain a second intermediate;
[0025] performing a second sintering treatment on the second intermediate to obtain a double alkali metal manganese-rich matrix;
[0026] Wherein, the dopant includes an M source, or the dopant includes an M source and a D source;
[0027] The mass ratio of the lithium element in the lithium salt solution to the first intermediate is (0.05-0.2):100;
[0028] The sintering temperature of the second sintering treatment is 300°C to 700°C.
[0029] In one embodiment, the lithium salt in the lithium salt solution includes one or more of lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide and lithium bis(oxalatoborate).
[0030] In one embodiment, the mass ratio of water in the lithium salt solution to the first intermediate is (1-5):1.
[0031] In one embodiment, the conditions of the ion exchange treatment include: a temperature of 0°C to 25°C and a time of 1 min to 10 min.
[0032] In one embodiment, the second intermediate is subjected to a second sintering process, comprising the following steps:
[0033] The second intermediate is kept at 300° C. to 700° C. for 3 h to 15 h to obtain the double alkali metal manganese-rich matrix; or,
[0034] Mixing the second intermediate and the coating agent, and maintaining the temperature at 300° C. to 700° C. for 3 h to 15 h to form a coating layer on the double alkali metal manganese-rich substrate;
[0035] The coating agent includes one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
[0036] In one embodiment, the manganese-rich precursor includes one or more oxides, hydroxides, and salt compounds containing nickel, cobalt, and manganese.
[0037] In one embodiment, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium sulfate, lithium acetate, lithium oxalate, lithium chloride and lithium fluoride.
[0038] In one embodiment, the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium sulfate, sodium oxalate, sodium acetate, sodium chloride and sodium fluoride.
[0039] In one embodiment, the M source includes one or more oxides, hydroxides and salt compounds containing the M element, and the M element includes one or more of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr.
[0040] In one embodiment, the D source includes one or more of fluoride, chloride and sulfide.
[0041] In one embodiment, the first sintering process comprises the following steps:
[0042] Keep warm at 300℃~800℃ for 0h~10h, and keep warm at 800℃~1000℃ for 4h~20h.
[0043] In a third aspect of the present application, a positive electrode sheet is provided, comprising the positive electrode material as described above.
[0044] In a fourth aspect of the present application, a secondary battery is provided, comprising the positive electrode sheet as described above.
[0045] This application has at least the following beneficial effects:
[0046] The modified lithium-rich manganese-based material provided in the present application includes a double alkali metal manganese-rich matrix, which introduces Na into the traditional lithium-rich manganese-based material. + Replacement part Li + , so that the O3 layered phase of the matrix is partially converted into a unique P2 layered phase, which reduces the cost and improves the first coulombic efficiency of the material. At the same time, through the sodium-lithium exchange reaction, part of the Na in the P2 layered phase is converted into a unique P2 layered phase.+ Replaced by Li + and alkali metal vacancies, thereby forming a more stable spinel phase and reducing the Na + content and reduce residual alkali. Compared with the spinel coating constructed in situ on the surface of the material, the present application gradually introduces an appropriate amount of P2 layered phase and spinel phase into the matrix through an ion exchange reaction. The interface compatibility between different crystal phases is good, and the destructiveness to the surface morphology and internal crystal structure of the matrix is small, which accelerates the lithium ion transfer kinetics, thereby effectively improving the rate performance, structural stability and cycle stability. Therefore, the double alkali metal manganese-rich matrix of the present application has a three-phase composite structure of O3 layered phase-P2 layered phase-spinel phase, and is matched with an appropriate amount of M element and D element, so that the modified lithium-rich manganese-based material has the advantages of high first coulomb efficiency, high discharge capacity, good rate performance, excellent cycle stability and low cost, which is very suitable as a positive electrode material for secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0048] Figure 1 Schematic diagram of a process for preparing a modified lithium-rich manganese-based material in one embodiment;
[0049] Figure 2 This is the XRD pattern of the modified lithium-rich manganese-based material of Example 2;
[0050] Figure 3 This is the XRD pattern of the modified lithium-rich manganese-based material of Comparative Example 3;
[0051] Figure 4 This is the XRD pattern of the modified lithium-rich manganese-based material of Comparative Example 6;
[0052] Figure 5 This is a first cycle charge and discharge curve diagram of the button-type half-cell of Example 2;
[0053] Figure 6 The first cycle charge and discharge curve of the button half-cell of Comparative Example 3;
[0054] Figure 7 The figure is a graph showing the change in cyclic discharge capacity of button-type half-cells of Example 2 and Comparative Example 3. DETAILED DESCRIPTION
[0055] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0057] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0058] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0059] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0060] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0061] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0062] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0063] In the present application, the layered transition metal oxide is a layered structure formed by alternating transition metal layers and alkali metal layers, which can be divided into P2 layered phase and O3 layered phase according to the arrangement and stacking order of oxygen atoms. Among them, P and O represent that the coordination environment of the alkali metal is a triangular prism and an octahedron, respectively, and the numbers 2 and 3 represent the stacking number of the minimum repeating unit of the oxygen layer. Compared with the O3 layered phase, the P2 layered phase has a lower diffusion barrier and higher ionic conductivity, which is beneficial to improve the first coulomb efficiency and rate performance of the material, and the electrical performance is better. In addition, the P2 layered phase has a lower diffusion barrier and a higher ionic conductivity than the O3 layered phase ... + There will be no oxygen layer slip during the deintercalation process, and the structure is more stable.
[0064] Lithium-rich manganese-based materials can be regarded as continuous solid solutions composed of Li2MnO3 and LiMO2 in different proportions, where M is Ni, Co or Mn. Lithium-rich manganese-based materials have high manganese content and low nickel and cobalt content, and are less expensive than cobalt-based materials (such as lithium cobalt oxide) and high nickel-based materials. Lithium-rich manganese-based materials have two charge compensation mechanisms, anion and cation, with a theoretical specific capacity of more than 250mAh / g, and have the advantages of high operating voltage, high safety and low pollution. They are regarded as the ideal choice for the next generation of lithium-ion battery positive electrode materials. However, lithium-rich manganese-based materials also have problems such as high cost due to the larger amount of lithium used, low first coulomb efficiency, and poor cycle performance.
[0065] In terms of cost, the lithium content in lithium-rich manganese-based materials is 20% to 50% higher than that of conventional nickel-cobalt-manganese ternary materials. The cost advantage brought by low-priced manganese-rich materials is gradually weakened by the increase in lithium salt prices. In terms of material performance, lithium-rich manganese-based materials will be accompanied by the release of lattice oxygen during the charging and discharging process, and their layered structure will transform into a spinel structure and then into a rock salt structure, resulting in a decrease in structural stability. The evolution of these crystal structures causes lithium-rich manganese-based materials to show a large first irreversible capacity loss (i.e., low first coulomb efficiency) in electrochemical performance, structural degradation during the cycle, resulting in severe capacity and voltage attenuation, poor kinetics, resulting in poor rate performance, and poor high-temperature storage performance. Many problems have hindered its commercial application process.
[0066] Based on this, in the first aspect of the present application, a modified lithium-rich manganese-based material is provided to overcome the problems of low first coulombic efficiency, poor rate performance, poor cycle performance and high cost existing in traditional lithium-rich manganese-based materials.
[0067] In some embodiments, the modified lithium-rich manganese-based material includes a double alkali metal manganese-rich matrix;
[0068] The expression of the double alkali metal manganese-rich matrix is: Li 1+x Na z Mn a Co b Ni c M 1-a-b-c O 2+x+z-y D y ;
[0069] Among them, 0 <x<0.5,0<z<0.2,0≤y≤0.1;
[0070] 0.6≤a≤0.75, 0≤b≤0.1, 0.25≤c≤0.4, 0<1-abc≤0.05;
[0071] The M element includes one or more of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr;
[0072] The D element includes one or more of F, Cl and S;
[0073] The double alkali metal manganese-rich matrix has an O3 layered phase, a P2 layered phase and a spinel phase. The total mass fraction of the P2 layered phase and the spinel phase in the double alkali metal manganese-rich matrix is 1%~15%.
[0074] The modified lithium-rich manganese-based material provided in the present application includes a double alkali metal manganese-rich matrix, which introduces Na into the traditional lithium-rich manganese-based material. + Replacement part Li + , so that the O3 layered phase of the matrix is partially converted into a unique P2 layered phase, which reduces the cost and improves the first coulombic efficiency of the material. At the same time, through the sodium-lithium exchange reaction, part of the Na in the P2 layered phase is converted into a unique P2 layered phase. + Replaced by Li + and alkali metal vacancies, thereby forming a more stable spinel phase and reducing the Na +content and reduce residual alkali. Compared with the spinel coating constructed in situ on the surface of the material, the present application gradually introduces an appropriate amount of P2 layered phase and spinel phase inside the matrix through an ion exchange reaction. The interface compatibility between different crystal phases is good, and the destructiveness to the surface morphology and internal crystal structure of the matrix is small, which accelerates the lithium ion transfer dynamics, thereby effectively improving the rate performance, structural stability and cycle stability. Therefore, the double alkali metal manganese-rich matrix of the present application has a three-phase composite structure of O3 layered phase-P2 layered phase-spinel phase, and is matched with an appropriate amount of M element and D element doping, so that the modified lithium-rich manganese-based material has the advantages of high first coulomb efficiency, high discharge capacity, good rate performance, excellent cycle stability and low cost, which is very suitable as a positive electrode material for secondary batteries.
[0075] It can be understood that x, y, z, a, b and c represent the stoichiometric ratios of the corresponding elements in the double alkali metal manganese-rich matrix. Limiting the content of each element is beneficial to reduce the introduction of Na + The negative impact brought about by this can be avoided, and problems such as excessive residual alkali in the material, poor structural stability and decreased dynamics can be avoided.
[0076] As an example, the value of x includes, but is not limited to, 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45 or 0.49. Further optionally, 0.2≤x≤0.3.
[0077] As an example, the value of z includes but is not limited to 0.01, 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18 or 0.20. Further optionally, 0.05≤z≤0.15.
[0078] In this application, by limiting the values of x and z, the Li + and Na + The molar ratio is beneficial to regulate the mass proportion of the three crystalline phases and avoid Li + Dona + Too little to achieve the goal of reducing construction costs and reducing Li + Shao Na + The defects of low discharge capacity and excessive residual alkali on the surface are caused by many factors.
[0079] As an example, the value of y includes but is not limited to 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.10. Further optionally, 0≤y≤0.05.
[0080] In the present application, doping with an appropriate amount of D element is beneficial to promoting the anion redox reversibility and improving the first coulombic efficiency.
[0081] As an example, the value of a includes, but is not limited to, 0.60, 0.62, 0.64, 0.66, 0.68, 0.70, 0.71, 0.72, 0.73, 0.74 or 0.75. Further optionally, 0.63≤a≤0.7.
[0082] As an example, the value of b includes but is not limited to 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1. Further optionally, 0.01≤b≤0.08.
[0083] As an example, the value of c includes but is not limited to 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.32, 0.34, 0.36, 0.38 or 0.40. Further optionally, 0.28≤x≤0.35.
[0084] In the present application, by limiting the values of a and c, the molar ratio of Ni and Mn in the double alkali metal manganese-rich oxide can be limited, which can avoid the influence of Ni on Na + The embedding of Ni can reduce the residual alkali on the surface and improve the structural stability. On the other hand, it can reduce the defects of kinetic decline caused by less Ni and more Mn.
[0085] As an example, the value of 1-abc includes but is not limited to 0.001, 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045 or 0.05. Further optionally, 0.005≤1-abc≤0.025.
[0086] In the present application, the use of M element for doping is beneficial to improve the structural stability of the double alkali metal manganese-rich matrix and promote the capacity. Limiting 1-abc to less than 0.05 can ensure that the transition metal ion has a suitable doping amount, avoiding the defect of excessive doping amount causing the generation of impurities and resulting in a decrease in discharge capacity.
[0087] It can be understood that the M element can be selected from any one of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr, or a combination of two or more of the above elements. Further optionally, the M element includes one or more of Nb, W, Mo, Sb, Cr and Zr. On the one hand, the above elements can be doped in the surface interface to refine the grains, and on the other hand, they can be doped in the bulk phase to stabilize the stability of the bulk phase structure. Further optionally, Nb can be further selected.
[0088] It can be understood that the D element can be selected from one of F, Cl and S, or a combination of two or more of the above non-metallic elements. Further optionally, the D element is F.
[0089] Optionally, the P2 layered phase is uniformly dispersed in the double alkali metal manganese-rich matrix and is in close contact with the O3 layered phase; the distribution concentration of the spinel phase gradually decreases in the direction pointing inward along the surface of the double alkali metal manganese-rich matrix.
[0090] It can be understood that in the double alkali metal manganese-rich matrix, the mass fraction of the O3 layered phase reaches more than 85%, which is the main crystal phase structure of the matrix. The P2 layered phase is formed by the introduction of sodium elements, can be evenly dispersed in the matrix, and is in close contact with the O3 layered phase. The spinel phase is transformed from part of the P2 layered phase through a sodium-lithium exchange reaction from the surface to the inside, and its distribution concentration shows a gradient decreasing trend from the surface of the matrix to the inside of the matrix. The spinel phase has a very high distribution concentration on the surface of the matrix, and it can be approximately considered that the surface of the matrix has a continuous or discontinuous spinel coating.
[0091] As an example, the total mass fraction of the P2 layered phase and the spinel phase in the double alkali metal manganese-rich matrix includes but is not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, and can be further optionally 8% to 12%.
[0092] In the present application, according to the formation mechanism of the three-phase composite structure, the spinel phase is transformed from part of the P2 layered phase by a sodium-lithium exchange reaction, and the P2 layered phase is formed by using Na + Replacement part Li + It is transformed from part of the O3 layered phase, so it can be based on the Na before the sodium-lithium exchange reaction. + The total mass fraction of P2 layered phase and spinel phase in the double alkali metal manganese-rich matrix was estimated by the content of P2 layered phase and spinel phase.
[0093] The total mass fraction of the P2 layered phase and the spinel phase is too low to achieve the effect of reducing costs and increasing efficiency. The higher the total mass fraction of the P2 layered phase and the spinel phase, the less lithium ions are used, but it will affect the capacity of the modified lithium-rich manganese-based material. Limiting the total mass fraction of the P2 layered phase and the spinel phase to 1%~15% can well balance the cost, first coulomb efficiency, rate performance and cycle performance, and greatly improve the comprehensive performance of the modified lithium-rich manganese-based material.
[0094] Optionally, the X-ray diffraction pattern (XRD pattern) of the double alkali metal manganese-rich matrix satisfies the following conditions:
[0095] (1) There is a (003) crystal plane diffraction peak at 2θ=18°~19°, which belongs to the O3 layered phase;
[0096] (2) There is a (104) crystal plane diffraction peak at 2θ = 43°~46°, which belongs to the O3 layered phase, and the left side of the (104) crystal plane diffraction peak has a shoulder peak or broadening belonging to the spinel phase;
[0097] (3) There is a diffraction peak at 2θ = 15.2°~16.2°, which belongs to the P2 layered phase;
[0098] (4) There is a superlattice diffraction peak at 2θ=20°~23°, which is attributed to Li2MnO3.
[0099] The XRD spectrum of the double alkali metal manganese-rich matrix shows that the double alkali metal manganese-rich matrix has a three-phase composite of O3 layered phase, P2 layered phase and spinel phase.
[0100] Optionally, the modified lithium-rich manganese-based material also includes a coating layer supported on the double alkali metal manganese-rich matrix, the coating layer including one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
[0101] Phosphate is used as a coating agent to form an ion conductor coating layer on the double alkali metal manganese-rich matrix. It not only has good structural stability, can reduce interface side reactions, inhibit the release of lattice oxygen in the material, and improve the structural stability and long cycle performance of the material, but also has a three-dimensional ion diffusion channel, which can conduct Li + Can also conduct Na + , excellent dynamics, ensuring Li + and Na + The rapid transmission of ions increases the discharge capacity, improves the ion diffusion rate and enhances the rate performance. At the same time, fluoride and oxide as coating agents help to inhibit interface side reactions and improve long cycle performance.
[0102] Optionally, the coating layer may further be one or more of aluminum phosphate, aluminum oxide and zirconium fluoride.
[0103] Optionally, the mass ratio of the double alkali metal manganese-rich matrix to the coating layer is 100:(0.05~2).
[0104] As an example, the mass ratio of the double alkali metal manganese-rich matrix and the coating layer includes but is not limited to 100:0.05, 100:0.08, 100:0.1, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:1.2, 100:1.5, 100:1.8 or 100:2, and can further be 100:(0.5~1.5).
[0105] It can be understood that the coating layer can be partially coated or completely coated on the substrate. The coating layer partially coats the substrate, which means that the coating layer is loaded on part of the surface of the substrate to form a dispersed island structure. The coating layer completely coats the core, which means that the coating layer is loaded on all surfaces of the substrate to form a continuous film structure, which has a more significant effect on improving structural stability and long cycle performance. By limiting the mass ratio of the double alkali metal manganese-rich substrate and the coating layer, the coating layer can form a good coating effect on the surface of the substrate, thereby improving the electrochemical properties of the material.
[0106] Optionally, the coating layer has a thickness of 5 nm to 20 nm.
[0107] As an example, the thickness of the coating layer includes, but is not limited to, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, or 20 nm.
[0108] Optionally, the D50 particle size of the modified lithium-rich manganese-based material is 2 μm to 15 μm.
[0109] As an example, the D50 particle size of the modified lithium-rich manganese-based material includes but is not limited to 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.
[0110] In a second aspect of the present application, a method for preparing a modified lithium-rich manganese-based material is provided, which is used to prepare the modified lithium-rich manganese-based material as described above.
[0111] See also Figure 1 , which is a schematic diagram of a process for preparing a modified lithium-rich manganese-based material in one embodiment. Figure 1 As shown, the preparation method of the modified lithium-rich manganese-based material comprises the following steps:
[0112] S100: mixing a manganese-rich precursor, a lithium source, a sodium source and a dopant, and performing a first sintering treatment to obtain a first intermediate;
[0113] S200: dispersing the first intermediate in a lithium salt solution to perform ion exchange treatment, and performing solid-liquid separation treatment and drying treatment to obtain a second intermediate;
[0114] S300: performing a second sintering treatment on the second intermediate to obtain a double alkali metal manganese-rich matrix;
[0115] Wherein, the dopant includes an M source, or the dopant includes an M source and a D source;
[0116] The mass ratio of lithium element in the lithium salt solution to the first intermediate is (0.05-0.2):100;
[0117] The sintering temperature of the second sintering treatment is 300°C to 700°C.
[0118] There are reports of in-situ construction of a more stable spinel structure on the surface of traditional lithium-rich manganese-based materials to improve rate performance and slow down voltage decay. The in-situ construction methods are mainly divided into three types: solid phase coating, wet coating and gas phase coating. However, solid phase coating cannot guarantee the coating uniformity and interface compatibility of the spinel structure. Wet coating and gas phase protection often need to be carried out in a redox environment or an acidic environment, which is severely destructive to the material surface, causing a drop in equalized pressure, that is, a decrease in energy density and deterioration of high temperature performance.
[0119] Compared with the in-situ construction method to form a coating layer with a spinel structure, the present application is to mix a manganese-rich precursor, a lithium source, a sodium source and a dopant and then perform a first sintering treatment, thereby achieving the doping of M and D elements and introducing an appropriate amount of Na + , prompting the first intermediate to form a two-phase composite structure with an O3 layered phase-P2 layered phase. Then, the first intermediate is used to carry out an ion exchange reaction in a lithium salt solution. By controlling the mass ratio of the lithium element in the lithium salt solution and the first intermediate, and undergoing solid-liquid separation treatment, drying treatment, and a second sintering treatment at a suitable temperature, part of the P2 layered phase can be prompted to be converted into a spinel phase, thereby forming a three-phase composite structure of an O3 layered phase-P2 layered phase-spinel phase. The preparation method provided in the present application can ensure that different crystalline phases have good interface compatibility, does not need to be carried out in a redox environment or an acidic environment, and has little destructiveness to the surface morphology and internal crystal structure of the material. Therefore, a modified lithium-rich manganese-based material with high first coulomb efficiency, high discharge capacity, good rate performance, excellent cycle stability, and low cost can be obtained, which is very suitable for large-scale production and commercial application.
[0120] The following is a detailed description of the preparation method of the modified lithium-rich manganese-based material in a step-by-step manner.
[0121] S100: mixing a manganese-rich precursor, a lithium source, a sodium source and a dopant, and performing a first sintering treatment to obtain a first intermediate.
[0122] Optionally, the manganese-rich precursor includes one or more of oxides, hydroxides, and salt compounds containing nickel, cobalt, and manganese, wherein the salt compound includes one or more of carbonates, oxalates, acetates, acetates, and fluorides. Further optionally, the manganese-rich precursor is a hydroxide containing nickel, cobalt, and manganese.
[0123] Optionally, the molar ratio of manganese, cobalt and nickel in the manganese-rich precursor is (0.6-0.75): (0-0.1): (0.25-0.4), that is, the molar ratio of manganese, cobalt and nickel in the manganese-rich precursor is the same as that in the double alkali metal manganese-rich matrix.
[0124] Optionally, the lithium source includes one or more of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), lithium acetate (CH3COOLi), lithium oxalate (Li2C2O4), lithium chloride (LiCl) and lithium fluoride (LiF), and further lithium carbonate (Li2CO3) may be selected. The raw material of the lithium source may contain bound water, such as lithium hydroxide monohydrate (LiOH•H2O) and lithium acetate monohydrate (CH3COOLi•H2O), or may not contain bound water, such as anhydrous lithium carbonate, anhydrous lithium hydroxide, anhydrous lithium acetate, etc.
[0125] Optionally, the sodium source includes one or more of sodium carbonate (Na2CO3), sodium hydroxide (NaOH), sodium sulfate (Na2SO4), sodium oxalate (Na2C2O4), sodium acetate (CH3COONa), sodium chloride (NaCl) and sodium fluoride (NaF), and further sodium carbonate (Na2CO3) may be selected. The raw material of the sodium source may also contain bound water, such as sodium carbonate monohydrate or sodium carbonate decahydrate, or may not contain bound water, such as anhydrous sodium carbonate.
[0126] Optionally, the M source includes one or more of an oxide, hydroxide and salt compound containing the M element, wherein the salt compound includes one or more of carbonate, oxalate, acetate, acetate and fluoride. Further optionally, the M source is an oxide containing the M element, such as one or more of CaO, Al2O3, BaO, CeO2, Cr2O3, CuO, Fe2O3, K2O, La2O3, MgO, MoO3, TeO2, Nb2O5, Sb2O5, Sm2O3, Ta2O5, TiO2, V2O5, WO3, Y2O5, SnO2, ZnO and ZrO2. Further optionally, the M source is one or more of Nb2O5, WO3, MoO3, Sb2O5, Cr2O3 and ZrO2.
[0127] Optionally, the D source includes one or more of fluoride, chloride and sulfide. Among them, the fluoride includes one or more of NaF, LiF, KF and NH4F; the chloride includes one or more of NaCl, LiCl, KCl and NH4Cl; the sulfide includes one or more of Li2S, Na2S and CH4N2S. Further optionally, the D source is a fluoride. Further optionally, the D source is NH4F.
[0128] Optionally, the molar ratio of lithium element in the lithium source to the transition metal element in the manganese-rich precursor is: d / (a+b+c)=1.1~1.5; the molar ratio of sodium element in the sodium source to the transition metal element in the manganese-rich precursor is e / (a+b+c)=0.03~0.3; the molar ratio of M element in the M source to the transition metal element in the manganese-rich precursor is (1-abc) / (a+b+c)=0~0.05; the molar ratio of D element in the D source to the transition metal element in the manganese-rich precursor is y / (a+b+c)=0~0.1.
[0129] Na in the first intermediate + The content is the key factor in determining the total mass fraction of the P2 layered phase and the spinel phase. + The ionic radius is larger than Li + The ionic radius is large, and during the synthesis of the first intermediate, Na + Compared with Li + It is more difficult and requires an additional concentration difference to provide a diffusion driving force. + 、Na + Will react with Li in water + , H +Ion exchange is performed to reduce the alkali metal content in the second intermediate, and ultimately affect the content of the three crystalline phases in the double alkali metal manganese-rich matrix. Therefore, the sodium source should be appropriately excessive so that the alkali metal content of the second intermediate is consistent with the alkali metal content of the target expression, and a double alkali metal manganese-rich matrix with a total mass fraction of the P2 layered phase and the spinel phase of 1% to 15% is obtained.
[0130] Optionally, the first sintering treatment adopts a staged sintering treatment, which includes the following steps: keeping warm at 300°C-800°C for 0h-10h, and keeping warm at 800°C-1000°C for 4h-20h.
[0131] The sintering temperature of the first sintering treatment should not be too high. This is because at too high a sintering temperature, the sintered product will grow excessively, resulting in an increase in the particle size and excessive density of the first intermediate, which is not conducive to subsequent ion exchange treatment and the formation of the spinel phase, thereby having a negative impact on the electrochemical performance.
[0132] As an example, the first sintering temperature of the first sintering treatment includes but is not limited to 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃ or 800℃, and may be further selected as 350℃~750℃, and may be further selected as 450℃~550℃.
[0133] As an example, the holding time of the first sintering treatment at the first sintering temperature includes but is not limited to 0h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, and can further be 4h~8h.
[0134] As an example, the second sintering temperature of the first sintering treatment includes but is not limited to 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C or 1000°C, and may be further optionally 900°C to 1000°C, and further optionally 940°C to 960°C.
[0135] As an example, the holding time of the first sintering treatment at the second sintering temperature includes but is not limited to 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, and can be further optionally 8h~15h.
[0136] Optionally, in the first sintering treatment, the heating rate from room temperature to the first sintering temperature and the heating rate from the first sintering temperature to the second sintering temperature are each independently 1°C / min to 10°C / min, including but not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0137] Optionally, the first sintering process is performed in an oxygen-containing atmosphere, such as an air atmosphere and an oxygen atmosphere.
[0138] S200: dispersing the first intermediate in a lithium salt solution for ion exchange treatment, and performing solid-liquid separation treatment and drying treatment to obtain a second intermediate.
[0139] Na + The ionic radius is larger than Li + The first intermediate is dispersed in a lithium salt solution for ion exchange treatment. The Na + Sodium-lithium exchange can occur directly. As the ion exchange reaction proceeds, the Na + It will also participate in sodium-lithium exchange, and the ion exchange amount gradually decreases from the surface to the inside. Through ion exchange treatment, the Na + The content of Li + Occupy Na + After the second sintering treatment, the part of the P2 layered phase that undergoes ion exchange eventually transforms into a spinel phase, which is beneficial to improving the interface stability and structural stability and accelerating the lithium ion transfer kinetics. In addition, the ion exchange treatment is carried out in a neutral or alkaline lithium salt solution, which will not cause any structural damage to the material.
[0140] Optionally, the lithium salt in the lithium salt solution includes one or more of lithium hydroxide (LiOH), lithium nitrate (LiNO3), lithium acetate (CH3COOLi), lithium oxalate (Li2C2O4), lithium fluoride (LiF), lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide (LiI) and lithium bis(oxalatoborate) (LiBC4O8, LiBOB), and may further be selected from one or more of lithium hydroxide (LiOH), lithium nitrate (LiNO3), lithium acetate (CH3COOLi) and lithium chloride (LiCl), and may further be selected from lithium hydroxide (LiOH).
[0141] It can be understood that the raw materials of lithium salts in lithium salt solutions may contain bound water, such as lithium hydroxide monohydrate (LiOH•H2O) and lithium acetate monohydrate (CH3COOLi•H2O), etc., or may not contain bound water, such as anhydrous lithium carbonate, anhydrous lithium hydroxide, anhydrous lithium acetate, etc. The lithium salt in the lithium salt solution has good water solubility and can be ionized in an aqueous solution to form Li + , which is conducive to sufficient ion exchange reaction with the first intermediate.
[0142] Optionally, the pH value of the lithium salt solution is 7-13.
[0143] As an example, the pH value of the lithium salt solution includes, but is not limited to, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5 or 13, and may further be 7 to 10.
[0144] Optionally, the mass ratio of the lithium element in the lithium salt solution to the first intermediate is (0.05~0.2):100.
[0145] By controlling the mass ratio of lithium element in the lithium salt solution to the first intermediate, it is possible to ensure that the lithium salt solution contains an appropriate concentration of Li + , which is beneficial to control Li + and Na + The ion exchange rate is high, so that the material contains an appropriate amount of alkali metal vacancies and promotes the formation of spinel phase, thereby forming a modified lithium-rich manganese-based material with a three-phase composite structure.
[0146] As an example, the mass ratio of lithium element to intermediate in the lithium salt solution includes but is not limited to 0.05:100, 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.10:100, 0.11:100, 0.12:100, 0.13:100, 0.14:100, 0.15:100, 0.16:100, 0.17:100, 0.18:100, 0.19:100 or 0.2:100, and may further be (0.08~0.12):100.
[0147] Optionally, the mass ratio of water to the first intermediate in the lithium salt solution is (1~5):1.
[0148] By controlling the mass ratio of the solvent to the first intermediate in the lithium salt solution, it is possible to ensure that the lithium salt solution contains an appropriate concentration of Li + and H + , which is beneficial to control the ion exchange rate, thereby ensuring that the material has excellent structural stability and cycle stability.
[0149] As an example, the water in the lithium salt solution can be tap water, deionized water, pure water, ultrapure water, distilled water or reverse osmosis water, and can further be deionized water or pure water to reduce the introduction of impurities.
[0150] As an example, the mass ratio of water to the first intermediate in the lithium salt solution includes but is not limited to 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, and can be further optionally (1~2):1.
[0151] Optionally, the conditions of the ion exchange treatment include: a temperature of 0°C to 25°C and a time of 1 min to 10 min.
[0152] The temperature of ion exchange treatment should not be too high, because if the temperature is too high, the alkali metal ions and Li + and H + The degree of exchange is too high, especially the sodium-hydrogen exchange is excessive, which reduces the cycle stability; at the same time, the ion exchange treatment time is too long, which will reduce the actual production efficiency and cause the spinel phase content to be too high; while the ion exchange treatment time is too short, the lithium-sodium exchange effect is not obvious.
[0153] As an example, the temperature of the ion exchange treatment can be 0°C, 2°C, 5°C, 8°C, 10°C, 12°C, 15°C, 18°C, 20°C, 22°C, 24°C or 25°C, and can further be 5°C to 15°C.
[0154] As an example, the time of the ion exchange treatment can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, and can further be 2 min to 8 min.
[0155] Optionally, the solid-liquid separation treatment method includes one or more of suction filtration, filter press and centrifugation, and suction filtration can be further selected.
[0156] Optionally, the drying process comprises the following steps: drying at 90° C. to 200° C. for 10 h to 24 h.
[0157] As an example, the drying method includes one or more of air-blast drying and vacuum drying.
[0158] As an example, the temperature of the drying process can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, and can further be 90°C~150°C.
[0159] As an example, the drying time may be 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, and may further be 12 h to 18 h.
[0160] S300: performing a second sintering treatment on the second intermediate to obtain a double alkali metal manganese-rich matrix;
[0161] Optionally, the sintering temperature of the second sintering process is 300°C to 700°C.
[0162] If the sintering temperature of the second sintering treatment is too low, the alkali metal vacancies and oxygen vacancies cannot be repaired, and it is difficult to generate the spinel phase. If the sintering temperature of the second sintering treatment is too high, the alkali metal vacancies in the material will be transformed into an inert rock salt phase at an excessively high sintering temperature, thereby causing a decrease in discharge capacity. By controlling the sintering temperature of the second sintering treatment, the modified lithium-rich manganese-based material can be prompted to form a three-phase composite structure having an O3 layered phase-P2 layered phase-spinel phase.
[0163] Optionally, the second intermediate is subjected to a second sintering treatment, comprising the following steps: the second intermediate is kept at 300° C. to 700° C. for 3 h to 15 h to obtain a double alkali metal manganese-rich matrix.
[0164] As an example, the sintering temperature of the second sintering treatment may be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, further optionally 350°C to 750°C, further optionally 450°C to 550°C.
[0165] As an example, the holding time of the second sintering treatment can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, and can further be 8h~12h.
[0166] Optionally, in the second sintering treatment, the heating rate from room temperature to the sintering temperature is 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, and can be further optionally 2°C / min to 6°C / min.
[0167] Optionally, the second sintering process is performed in an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere.
[0168] Optionally, the second intermediate is subjected to a second sintering treatment, comprising the following steps: mixing the second intermediate and a coating agent, and keeping warm at 300°C to 700°C for 3h to 15h to form a coating layer on the double alkali metal manganese-rich matrix; wherein the coating agent includes one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
[0169] Optionally, the coating agent includes one or more of aluminum phosphate, aluminum oxide and zirconium fluoride.
[0170] In a third aspect of the present application, a positive electrode sheet is provided, comprising the positive electrode material as described above.
[0171] Optionally, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer covering the positive electrode current collector.
[0172] It can be understood that the positive electrode active layer covers at least one surface of the positive electrode current collector, and may cover only one surface or two opposite surfaces at the same time to form a structure in which the positive electrode active layer, the positive electrode current collector and the positive electrode active layer are stacked in sequence.
[0173] Optionally, the positive electrode current collector includes a metal foil or a composite current collector. The metal foil may be aluminum foil; the composite current collector includes a polymer substrate and a metal layer formed on the polymer substrate, the polymer substrate may be made of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE), and the metal layer may be made of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0174] Optionally, the positive electrode active layer includes a positive electrode material, a binder and a conductive agent. + and Na + The binder is used to improve the bonding strength between the positive electrode active layer and the positive electrode current collector, and the conductive agent is used to improve the conductive performance of the positive electrode active layer.
[0175] Optionally, the positive electrode material includes the modified lithium-rich manganese-based material as described above, or includes the modified lithium-rich manganese-based material prepared by the preparation method of the modified lithium-rich manganese-based material as described above.
[0176] It can be understood that the positive electrode material in the positive electrode active layer can be used alone, that is, the above-mentioned modified lithium-rich manganese-based material can be used alone, or two or more can be used in combination, that is, the above-mentioned modified lithium-rich manganese-based material can be used in combination with at least one of the positive electrode materials known in the art. As an example, the positive electrode materials known in the art include but are not limited to: lithium transition metal oxides, olivine-structured lithium-containing phosphates and their respective modified compounds. Among them, lithium transition metal oxides include but are not limited to: lithium cobalt oxides, such as LiCoO2; lithium nickel oxides, such as LiNiO2; lithium manganese oxides, such as LiMnO2 or LiMn2O4; lithium nickel cobalt oxide; lithium manganese cobalt oxide; lithium nickel manganese oxide; lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2(NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ); lithium nickel cobalt aluminum oxide, such as LiNi 0.85 Co 0.15 Al 0.05 O2; and modified compounds of the above-mentioned lithium transition metal oxides. Lithium-containing phosphates with an olivine structure include, but are not limited to: lithium iron phosphate (LiFePO4, LFP), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, etc.
[0177] Optionally, the binder includes at least one of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA).
[0178] Optionally, the conductive agent includes at least one of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.
[0179] Optionally, the preparation method of the positive electrode sheet includes the following steps: dispersing the positive electrode material, the conductive agent and the binder in an organic solvent to prepare a positive electrode slurry; covering the positive electrode slurry on at least one surface of the positive electrode current collector, and drying, rolling and cutting to obtain a positive electrode sheet. The organic solvent is selected from N-methylpyrrolidone (NMP); the solid content of the positive electrode slurry is 20% to 50%; the drying temperature is 100°C to 150°C, the time is 60min to 120min, and further optionally, drying at 120°C for 80min.
[0180] In a fourth aspect of the present application, a secondary battery is provided, comprising the positive electrode sheet as described above.
[0181] It can be understood that a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as Li + 、Na + ) is inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The diaphragm is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.
[0182] Optionally, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer covering at least one surface of the negative electrode current collector. The negative electrode current collector includes a metal foil or a composite current collector. The metal foil in the negative electrode current collector can be copper foil. The composite current collector in the negative electrode current collector is basically the same as the composite current collector selected for the positive electrode current collector, and will not be described in detail.
[0183] Optionally, the negative electrode active layer includes a negative electrode material, a binder and a conductive agent. The negative electrode material includes at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material; the binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS); the conductive agent includes at least one of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene, and carbon nanofibers.
[0184] It is understood that the electrolyte in the secondary battery can be liquid, gel or all-solid.
[0185] Optionally, the electrolyte adopts an electrolyte solution, which includes a lithium salt and an organic solvent. Among them, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate; the organic solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0186] Optionally, the electrolyte further includes additives, such as negative electrode film-forming additives, positive electrode film-forming additives, additives for improving battery overcharge performance, additives for improving battery high or low temperature performance, etc.
[0187] It is understandable that the separator can be a porous separator with good chemical stability and mechanical stability; at the same time, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.
[0188] Optionally, the material of the diaphragm includes at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0189] It can be understood that the secondary battery of the present application includes a battery cell form, a battery module form and a battery pack form. The shape of the secondary battery can be cylindrical, square or other arbitrary shapes.
[0190] Optionally, the positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0191] Optionally, the secondary battery may include an outer package for encapsulating the electrode assembly and the electrolyte. The outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate, etc.
[0192] Optionally, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more. The battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more.
[0193] Optionally, the battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices include, but are not limited to: mobile devices, such as mobile phones, tablet computers, and laptop computers; electric vehicles, such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.; electric trains; ships; satellites; and energy storage systems.
[0194] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0195] Example 1
[0196] Please refer to Table 1, the preparation method of the modified lithium-rich manganese-based material of this embodiment is as follows:
[0197] (1) uniformly mixing a manganese-rich precursor, a lithium source, a sodium source and a dopant to obtain a mixture;
[0198] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0199] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0200] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.25;
[0201] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.005, F / (Ni+Co+Mn)=0.02.
[0202] (2) The mixed material is placed in an atmosphere box furnace for the first sintering treatment: the temperature is increased from room temperature to 500°C at a heating rate of 5°C / min and kept at this temperature for 5 hours; the temperature is increased from 500°C to 950°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; the mixed material is naturally cooled to room temperature in the furnace to obtain the first intermediate, which is expressed as follows:
[0203] Li 1.25 Na 0.25 (Ni 0.33 Co 0.01 Mn 0.66 ) 0.995 Nb 0.005 O2.48 F 0.02 .
[0204] (3) Mixing the first intermediate with a lithium salt solution, wherein the lithium salt solution is composed of LiOH and deionized water, and the mass ratio of lithium element, deionized water and the first intermediate in the lithium salt solution is 0.05:200:100; performing ion exchange treatment under stirring conditions at a temperature of 10°C for 5 minutes; performing solid-liquid separation treatment by suction filtration, vacuum drying at 120°C for 12 hours, and crushing treatment to obtain a second intermediate with D50 = 10 μm.
[0205] (4) The second intermediate is heated from room temperature to 500°C at a heating rate of 5°C / min and kept at this temperature for 10 hours for a second sintering treatment; it is naturally cooled to room temperature in the furnace and passed through a 300-mesh sieve to obtain a modified lithium-rich manganese-based material, which is expressed as Li 1.244 Na 0.064 (Ni 0.33 Co 0.01 Mn 0.66 ) 0.995 Nb 0.005 O 2.288 F 0.02 (For the convenience of writing chemical formulas, keep three decimal places and round off to the nearest value).
[0206] Example 2
[0207] The difference between this embodiment and embodiment 1 is that the mass ratio of lithium element, deionized water and the first intermediate in the lithium salt solution is 0.1:200:100.
[0208] Example 3
[0209] The difference between this embodiment and embodiment 1 is that the mass ratio of lithium element, deionized water and the first intermediate in the lithium salt solution is 0.2:200:100.
[0210] Embodiments 4 to 8
[0211] Embodiments 4 to 8 are substantially the same as Embodiment 2, except that:
[0212] Example 4: The sintering temperature in step (4) is 700°C.
[0213] Example 5: The sintering temperature in step (4) is 400°C.
[0214] Example 6: The lithium salt in step (3) is LiCl.
[0215] Example 7: The lithium salt in step (3) is CH3COOLi.
[0216] Example 8: The lithium salt in step (3) is LiNO3.
[0217] Example 9
[0218] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0219] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.34 Mn 0.66 (OH)2;
[0220] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.24;
[0221] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.24;
[0222] Dopants: WO3 and NH4F, the molar ratio of each element satisfies: W / (Ni+Co+Mn)=0.01, F / (Ni+Co+Mn)=0.02.
[0223] Example 10
[0224] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0225] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.25 Mn 0.75 (OH)2;
[0226] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.40;
[0227] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.28;
[0228] Dopant: MoO3 and NH4F, the molar ratio of each element satisfies: Mo / (Ni+Co+Mn)=0.02, F / (Ni+Co+Mn)=0.02.
[0229] Embodiment 11
[0230] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0231] The manganese-rich precursor is nickel-cobalt-manganese hydroxide Ni 0.3 Mn 0.7 (OH)2;
[0232] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.30;
[0233] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.26;
[0234] Dopant: Sb2O5 and NH4F, the molar ratio of each element satisfies: Sb / (Ni+Co+Mn)=0.02, F / (Ni+Co+Mn)=0.02.
[0235] Example 12
[0236] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0237] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.37 Mn 0.63 (OH)2;
[0238] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.18;
[0239] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.22;
[0240] Doping agents: Cr2O3 and NH4F, the molar ratio of each element satisfies: Cr / (Ni+Co+Mn)=0.05, F / (Ni+Co+Mn)=0.02.
[0241] Embodiment 13
[0242] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0243] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.4 Mn 0.6 (OH)2;
[0244] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.13;
[0245] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.2;
[0246] Dopant: ZrO2 and NH4F, the molar ratio of each element satisfies: Zr / (Ni+Co+Mn)=0.005, F / (Ni+Co+Mn)=0.02.
[0247] Embodiment 14
[0248] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0249] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.3 Co 0.1 Mn 0.6 (OH)2;
[0250] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.22;
[0251] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.23;
[0252] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.01, F / (Ni+Co+Mn)=0.02.
[0253] Embodiment 15
[0254] The difference between this embodiment and embodiment 2 is that the raw materials in step (1) are different.
[0255] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0256] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0257] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.25;
[0258] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.005.
[0259] Example 16
[0260] The difference between this embodiment and embodiment 2 is that the water washing time is 10 minutes.
[0261] Embodiment 17
[0262] The difference between this embodiment and embodiment 2 is that the water washing time is 15 minutes.
[0263] Embodiment 18
[0264] The difference between this embodiment and embodiment 2 is that a coating agent is added in step (4), which is as follows:
[0265] Aluminum phosphate is used as the coating agent, and the mass ratio of the second intermediate to the coating agent is controlled to be 100:0.5. After the second intermediate and the coating agent are mixed, the temperature is increased from room temperature to 500°C at a heating rate of 5°C / min, and the temperature is kept for 10 hours for the second sintering treatment; the material is naturally cooled to room temperature in the furnace, and passed through a 300-mesh sieve to obtain a modified lithium-rich manganese-based material with a coating layer loaded on the surface of the modified lithium-rich manganese-based material.
[0266] Comparative Example 1
[0267] The difference between this comparative example and Example 2 is that in step (3), the lithium salt solution is replaced by a sulfuric acid solution, and the mass ratio of sulfuric acid, deionized water and the first intermediate in the sulfuric acid solution is 0.1:200:100.
[0268] Comparative Example 2
[0269] The difference between this comparative example and Example 2 is that in step (3), the lithium salt solution is replaced by hydrogen peroxide, and the mass ratio of H2O2, deionized water and the first intermediate in the hydrogen peroxide is 0.1:200:100.
[0270] Comparative Example 3
[0271] The difference between this comparative example and Example 2 is that in step (3), the lithium salt solution is replaced by deionized water, and the mass ratio of deionized water to the first intermediate is 200:100.
[0272] Comparative Example 4
[0273] The difference between this comparative example and Example 2 is that the mass ratio of lithium element, deionized water and the first intermediate in the lithium salt solution in step (3) is 0.3:200:100.
[0274] Comparative Example 5
[0275] The difference between this comparative example and Example 2 is that the sintering temperature in step (4) is 250°C.
[0276] Comparative Example 6
[0277] The difference between this comparative example and Example 2 is that the sintering temperature in step (4) is 800°C.
[0278] Comparative Example 7
[0279] The difference between this comparative example and Example 2 is that the raw materials in step (1) are different.
[0280] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.2 Mn 0.8 (OH)2;
[0281] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.49;
[0282] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.3;
[0283] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.005, F / (Ni+Co+Mn)=0.02.
[0284] Comparative Example 8
[0285] The difference between this comparative example and Example 2 is that the raw materials in step (1) are different.
[0286] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.45 Mn 0.55 (OH)2;
[0287] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.09;
[0288] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.19;
[0289] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.005, F / (Ni+Co+Mn)=0.02.
[0290] Comparative Example 9
[0291] The difference between this comparative example and Example 2 is that the raw materials in step (1) are different.
[0292] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0293] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0294] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.25;
[0295] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.06, F / (Ni+Co+Mn)=0.02.
[0296] Comparative Example 10
[0297] The difference between this comparative example and Example 2 is that: in step (1), no M source is added, and other raw materials remain the same, namely:
[0298] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0299] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0300] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.25;
[0301] Dopant: NH4F, the molar ratio of each element satisfies: F / (Ni+Co+Mn)=0.02.
[0302] Comparative Example 11
[0303] The difference between this comparative example and Example 2 is that no sodium source is added in step (1), and other raw materials remain the same, namely:
[0304] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0305] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0306] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.06, F / (Ni+Co+Mn)=0.02.
[0307] Comparative Example 12
[0308] The difference between this comparative example and Example 2 is that: there is too much sodium source in step (1), and the other raw materials remain the same, that is, there are:
[0309] Manganese-rich precursor: nickel-cobalt-manganese hydroxide Ni 0.33 Co 0.01 Mn 0.66 (OH)2;
[0310] Lithium source: lithium carbonate, the molar ratio of each element satisfies: Li / (Ni+Co+Mn)=1.25;
[0311] Sodium source: sodium carbonate, the molar ratio of each element satisfies: Na / (Ni+Co+Mn)=0.35;
[0312] Dopant: Nb2O5 and NH4F, the molar ratio of each element satisfies: Nb / (Ni+Co+Mn)=0.06, F / (Ni+Co+Mn)=0.02.
[0313] Test Case
[0314] The modified lithium-rich manganese-based material was tested as follows:
[0315] 1. Morphology test: measured using a scanning electron microscope (SEM) model SU 8010 from Hitachi, Japan. The results are shown in Figure 1 .
[0316] 2. Composition test: obtained by X-ray powder diffractometer (XRD) test, the results are shown in Figure 2 .
[0317] 3. Na element content: measured by using the Optima 7000 inductively coupled plasma atomic emission spectrometer (ICP-AES) of Perkin Elmer, USA.
[0318] 4. Free lithium content: obtained by potentiometric titration test using Swiss Metrohm Model 905 automatic potentiometric titrator.
[0319] 5. Total mass fraction of P2 layered phase and spinel phase: The Na content in the first intermediate was tested by ICP-AES, so as to estimate the total mass fraction of P2 layered phase and spinel phase in the double alkali metal manganese-rich matrix.
[0320] 6. Electrochemical performance test: The modified lithium-rich manganese-based material is used as the positive electrode material to make the positive electrode sheet, which is then assembled into a 2032 button cell for electrochemical performance testing.
[0321] (1) Preparation of positive electrode sheet: The modified lithium-rich manganese-based material is used as the positive electrode material, and is evenly dispersed in an appropriate amount of N-methylpyrrolidone with a mass ratio of 90:5:5 with a binder PVDF and a carbon black conductive agent Super-P to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, dried at 120°C, rolled, and punched to form a positive electrode sheet with a diameter of 13 mm. The loading amount of the modified lithium-rich manganese-based material in the positive electrode sheet is about 12 mg / cm 2 .
[0322] (2) Battery assembly: In an argon-filled glove box, a 2032-type button cell was assembled using a lithium sheet as the negative electrode, a polypropylene microporous membrane (Celgard 2400) as the separator, and 1 M LiPF6 / ethylene carbonate (EC) + dimethyl carbonate (DMC) as the electrolyte.
[0323] (3) Electrochemical performance test: At 25°C, the following electrochemical performance tests were conducted on the 2032 button cell using the Xinwei battery test system: ① Charge and discharge tests were conducted at 0.2C to evaluate the initial charge and discharge specific capacity and initial coulombic efficiency of the positive electrode material; ② Cycled 100 times (100T) at 1C to evaluate the cycle performance of the material; ③ Charge and discharge tests were conducted at 0.2C, 0.33C, 0.5C, and 1C to evaluate the rate performance of the material. The battery's charge and discharge voltage window is 2.5V~4.55V, and the charge and discharge current density of 1C (1 times the rated capacity) is 230mA / g.
[0324] 6. Result analysis:
[0325] The above test results are shown in Table 3 and Figures 2 to 7 .in, Figure 2 is the XRD diagram of the modified lithium-rich manganese-based material of Example 2, Figure 3 is the XRD diagram of the modified lithium-rich manganese-based material of Comparative Example 3, Figure 4 is the XRD diagram of the modified lithium-rich manganese-based material of Comparative Example 6, Figure 5 This is a first cycle charge and discharge curve diagram of the button-type half-cell of Example 2; Figure 6 The first cycle charge and discharge curve of the button half-cell of Comparative Example 3; Figure 7 The figure is a graph showing the change in cyclic discharge capacity of button-type half-cells of Example 2 and Comparative Example 3.
[0326] Depend on Figure 2It can be seen that in the XRD spectrum of the modified lithium-rich manganese-based material of Example 2, the main strong peak (2θ=18°~19°) belongs to the (003) crystal plane diffraction peak of the O3 layered phase, the secondary strong peak (2θ=43°-46°) belongs to the (104) crystal plane diffraction peak of the O3 layered phase, and the left side of the secondary strong peak has a shoulder peak or broadening belonging to the spinel phase, at 2θ=15.2°~16.2° there is a diffraction peak belonging to the P2 layered phase, and near 2θ=21° there is a lithium-rich superlattice diffraction peak belonging to Li2MnO3, which proves that the modified lithium-rich manganese-based material of Example 2 has a three-phase composite structure of O3 layered phase-P2 layered phase-spinel phase.
[0327] Depend on Figure 3 It can be seen that in the XRD spectrum of the modified lithium-rich manganese-based material of Comparative Example 3, the diffraction peak of the P2 layered phase (2θ=15.2°~16.2°) is clearly visible, and no shoulder peak or broadening is observed on the left side of the secondary peak (2θ=43°-46°), that is, there is no spinel phase, indicating that the modified lithium-rich manganese-based material of Comparative Example 1 has a two-phase composite structure of O3 layered phase-P2 layered phase. Figure 2 and Figure 3 From the comparison, it can be seen that after the modified lithium-rich manganese-based material of Example 2 is treated with ion exchange of lithium salt solution, the characteristic peak intensity of the P2 layered phase is significantly reduced, and the lithium-rich superlattice diffraction peak (Li2MnO3) near 2θ=21° is still well preserved, indicating that the spinel phase is transformed from part of the P2 layered phase.
[0328] Depend on Figure 4 It can be seen that in the XRD spectrum of the modified lithium-rich manganese-based material of Comparative Example 6, the diffraction peak of the P2 layered phase (2θ=15.2°~16.2°) basically disappeared, and an inert rock salt phase was produced, which caused the first coulomb efficiency in the electrical performance test to drop significantly, and the cycle performance was further deteriorated. This shows that the second sintering treatment at a suitable temperature can cause the modified lithium-rich manganese-based material to form a three-phase composite structure with an O3 layered phase-P2 layered phase-spinel phase.
[0329] Taking Example 2 and Comparative Example 3 as examples, the mass fractions of the P2 layered phase and the spinel phase of the modified lithium-rich manganese-based material are estimated by the following method: the P2 phase content is designed according to Li / (Ni+Co+Mn). Ni is used in both Example 2 and Comparative Example 3. 0.33 Co 0.01 Mn 0.66(OH)2 is used as a manganese-rich precursor, and Li / (Ni+Co+Mn)=1.25 corresponds to a P2 layered phase with a mass fraction of 10% (the amount of lithium added is reduced by 10% compared to pure lithium-rich manganese-based materials that do not contain Na); Comparative Example 3 is washed with deionized water, and the synthesized material is a two-phase composite structure of a P2 layered phase-O3 layered phase, and the Na content contained therein corresponds to a P2 layered phase with a mass fraction of 10%. In Example 2, a lithium salt solution is used for ion exchange to replace part of the sodium ions, and a three-phase composite structure is formed after a secondary heat treatment, wherein the proportion of the P2 layered phase is determined by the ratio of the sodium content of Example 2 to the sodium content of Comparative Example 3 in Table 3, and the proportion of the spinel phase is determined by the ratio of the reduced sodium content of Example 2 to the sodium content of Comparative Example 3. The mass fractions of the P2 layered phase and the spinel phase in other embodiments and comparative examples are estimated by similar methods, which will not be repeated here.
[0330] It can be seen from Table 3 that compared with the comparative example 3 which uses deionized water for washing, the modified lithium-rich manganese-based materials of Examples 1 to 18 have significantly reduced sodium content and free lithium, indicating that the residual alkali on the surface of the material is significantly reduced, which is beneficial to inhibiting gas production and reducing interface impedance during the long cycle process.
[0331] Example 2 and Comparative Examples 1-2 compare the effects of lithium salt solution, sulfuric acid solution and hydrogen peroxide solution on ion exchange treatment. The comparison shows that after washing with dilute strong acid and strong oxidant, the sodium ion content of the modified lithium-rich manganese-based material decreases significantly, but the capacity, first coulombic efficiency, rate performance and cycle performance are seriously deteriorated. This is because excessive sodium / hydrogen exchange leads to excessive sodium release, collapse of the alkali metal layer structure, and secondary sintering to form an inert rock salt phase, which ultimately hinders the diffusion and migration of lithium ions.
[0332] Examples 1-3 and Comparative Examples 3-4 compare the effects of different concentrations of lithium salt solutions on ion exchange treatment. Comparative Example 3 does not use a lithium salt solution, but uses deionized water for washing. The product forms a two-phase composite structure of O3 layered phase-P2 layered phase. The sodium content of the P2 layered phase is relatively high. Although the initial coulombic efficiency is high, the cycle stability is relatively poor; the lithium salt dosage of Comparative Example 4 is too high. Although the sodium content is further reduced, the charge and discharge capacity is reduced and the free lithium increases. This is because the excess lithium ions that have not undergone lithium / sodium exchange exist on the surface in the form of residual lithium, resulting in an increase in initial impedance. At the same time, there are too few alkali metal vacancies in the material, which is not conducive to the formation of spinel phase, and excessive lithium dosage is contrary to the original intention of reducing costs.
[0333] The comparison between Examples 2, 4-5 and Comparative Examples 5-6 shows that the temperature of the second sintering treatment is crucial to the formation of the three-phase composite structure. If the temperature of the second sintering treatment is too low, the alkali metal vacancies and oxygen vacancies cannot be repaired and the three-phase composite structure cannot be formed, and the effect of improving the rate and cycle cannot be achieved. If the temperature of the second sintering treatment is too high, the spinel phase will continue to be converted into an inert rock salt phase, hindering the diffusion of lithium ions, resulting in deterioration of the capacity, rate and cycle performance.
[0334] Examples 2, 6 to 8 use different soluble lithium salts, respectively, and can achieve similar modification effects, indicating that the modification is caused by the lithium / sodium exchange reaction between the lithium ions in the lithium salt solution and the sodium ions of the first intermediate, while the anions in the lithium salt solution have little effect.
[0335] Comparison of Examples 2, 9-14 and Comparative Examples 7-8 shows that when the Mn content is too high, the kinetics will decrease, and thus the capacity and rate performance will decrease significantly; and when the Mn content is too low, although the kinetics are improved, the lithium-rich phase and the sodium-rich phase are insufficient, resulting in a decrease in the first coulombic efficiency, a decrease in capacity, and a deterioration in the cycle stability.
[0336] Comparison between Example 15 and Example 2 shows that the introduction of the F element reduces the valence state of Mn and promotes capacity development, but at the same time, the TM-F bond (the chemical bond between the transition metal element and the fluorine element) has a higher bond energy than the TM-O bond (the chemical bond between the transition metal element and the oxygen element), so the cycle stability is not significantly affected.
[0337] The electrical performance tests of Examples 16 to 17 are close to those of Example 2, indicating that the extension of ion exchange time at low temperature has little effect on material properties, but considering the actual production efficiency, it is not recommended.
[0338] The comparison between Example 18 and Example 2 shows that after the coating layer is formed on the surface of the double alkali metal manganese-rich substrate, the cycle stability is further enhanced due to the improvement of the material interface stability.
[0339] The comparison between Comparative Examples 9-10 and Example 2 shows that the electrical performance will decrease if the doping amount is too high or too low. Comparative Example 11 is too low in overall alkali metals, resulting in severe lithium deficiency in the material and unable to form a layered phase normally. Comparative Example 12 is still high in residual alkali due to the addition of a large amount of sodium, which affects the long-cycle performance of the material; in Comparative Example 13, the ratio of P2 layered phase to spinel phase reaches 16%, with less lithium and more sodium, resulting in deteriorated capacity, increased residual alkali, and decreased cycle.
[0340] Table 1. Raw materials for the first intermediate
[0341]
[0342] Note: The molar ratio of NCM refers to the molar ratio of Ni, Co and Mn; TM refers to transition metal elements, for example, Li / TM means Li / (Ni+Co+Mn).
[0343] Table 2. Ion exchange treatment and second sintering treatment
[0344]
[0345] Table 3. Properties of modified lithium-rich manganese-based materials
[0346]
[0347] Note: “ / ” indicates that it cannot be estimated; among them, Comparative Examples 1~2 cannot be estimated because of excessive sodium-hydrogen exchange, which forms an inert rock salt phase after secondary sintering; Comparative Example 6 cannot be estimated because the sintering temperature is too high, resulting in the conversion of the spinel phase into the inert rock salt phase; Comparative Example 11 cannot be estimated because no Na is introduced to produce the P2 layered phase and cannot be converted into the spinel phase.
[0348] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0349] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A modified lithium-rich manganese-based material, characterized in that: including a double alkali metal manganese-rich matrix; The double alkali metal manganese-rich matrix is expressed as: Li 1+x Na z Mn a Co b Ni c M 1-a-b-c O 2+x+z-y D y ; Among them, 0 <x<0.5,0<z<0.2,0≤y≤0.1; 0.6≤a≤0.75, 0≤b≤0.1, 0.25≤c≤0.4, 0<1-abc≤0.05; The M element includes one or more of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr; The D element includes one or more of F, Cl and S; The double alkali metal manganese-rich matrix comprises an O3 layered phase, a P2 layered phase and a spinel phase, and the total mass fraction of the P2 layered phase and the spinel phase in the double alkali metal manganese-rich matrix is 1% to 15%.
2. The modified lithium-rich manganese-based material according to claim 1, characterized in that: The P2 layered phase is uniformly dispersed in the double alkali metal manganese-rich matrix and is in close contact with the O3 layered phase; The distribution concentration of the spinel phase gradually decreases in the direction pointing inward along the surface of the double alkali metal manganese-rich matrix.
3. The modified lithium-rich manganese-based material according to claim 1, characterized in that: The X-ray diffraction pattern of the double alkali metal manganese-rich matrix meets the following conditions: (1) There is a (003) crystal plane diffraction peak at 2θ=18°~19°, which belongs to the O3 layered phase; (2) There is a (104) crystal plane diffraction peak at 2θ = 43°~46°, which belongs to the O3 layered phase, and the left side of the (104) crystal plane diffraction peak has a shoulder peak or broadening belonging to the spinel phase; (3) There is a diffraction peak at 2θ = 15.2°~16.2°, which belongs to the P2 layered phase; (4) There is a superlattice diffraction peak at 2θ=20°~23°, which is attributed to Li2MnO3.
4. The modified lithium-rich manganese-based material according to any one of claims 1 to 3, characterized in that: The M element includes one or more of Nb, W, Mo, Sb, Cr and Zr.
5. The modified lithium-rich manganese-based material according to any one of claims 1 to 3, characterized in that: The modified lithium-rich manganese-based material also includes a coating layer supported on the double alkali metal manganese-rich matrix, and the coating layer includes one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
6. A method for preparing a modified lithium-rich manganese-based material according to any one of claims 1 to 5, characterized in that: The following steps are involved: A manganese-rich precursor, a lithium source, a sodium source and a dopant are mixed and subjected to a first sintering treatment to obtain a first intermediate; Dispersing the first intermediate in a lithium salt solution for ion exchange treatment, and performing solid-liquid separation and drying treatment to obtain a second intermediate; performing a second sintering treatment on the second intermediate to obtain a double alkali metal manganese-rich matrix; Wherein, the dopant includes an M source, or the dopant includes an M source and a D source; The mass ratio of the lithium element in the lithium salt solution to the first intermediate is (0.05-0.2):100; The sintering temperature of the second sintering treatment is 300°C to 700°C.
7. The method for preparing the modified lithium-rich manganese-based material according to claim 6, characterized in that: One or more of the following conditions are met: (1) The lithium salt in the lithium salt solution includes one or more of lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide and lithium bis(oxalatoborate); (2) The mass ratio of water in the lithium salt solution to the first intermediate is (1-5):1; (3) The conditions of the ion exchange treatment include: temperature of 0°C to 25°C and time of 1 min to 10 min.
8. The method for preparing a modified lithium-rich manganese-based material according to any one of claims 6 to 7, characterized in that: The second intermediate is subjected to a second sintering treatment, comprising the following steps: Mixing the second intermediate and the coating agent, and keeping the mixture at 300° C. to 700° C. for 3 h to 15 h to form a coating layer on the double alkali metal manganese-rich substrate; The coating agent includes one or more of phosphates, fluorides and oxides containing R elements, and the R elements include one or more of Li, Na, K, V, Cr, Mn, Co, Ni, Mg, Al, Zr, W, Mo, Ce, La and Y.
9. The method for preparing the modified lithium-rich manganese-based material according to claim 6, characterized in that: One or more of the following conditions are met: (1) The manganese-rich precursor includes one or more oxides, hydroxides, and salt compounds containing nickel, cobalt, and manganese; (2) The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium sulfate, lithium acetate, lithium oxalate, lithium chloride and lithium fluoride; (3) The sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium sulfate, sodium oxalate, sodium acetate, sodium chloride and sodium fluoride; (4) The M source includes one or more oxides, hydroxides and salt compounds containing the M element, and the M element includes one or more of Ca, Al, Ba, Ce, Cr, Cu, Fe, K, La, Mg, Mo, Te, Nb, Sb, Sm, Ta, Ti, V, W, Y, Sn, Zn and Zr; (5) The D source includes one or more of fluoride, chloride and sulfide.
10. The method for preparing the modified lithium-rich manganese-based material according to claim 6, characterized in that: The first sintering process comprises the following steps: Keep warm at 300℃~800℃ for 0h~10h, and keep warm at 800℃~1000℃ for 4h~20h.
11. A positive electrode sheet, characterized in that: The modified lithium-rich manganese-based material comprises the modified lithium-rich manganese-based material as described in any one of claims 1 to 5, or the modified lithium-rich manganese-based material prepared by the preparation method of the modified lithium-rich manganese-based material as described in any one of claims 6 to 10.
12. A secondary battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.
Citation Information
Patent Citations
Layered manganese-based composite material for power-type lithium ion battery and preparation method thereof
CN102255083A
Lithium-rich manganese-based positive electrode active material and battery
CN116190631A
Modified sodium ion battery positive electrode material, preparation method thereof and battery
CN116730407A
Modified lithium-rich manganese-based material, preparation method, positive electrode material, positive electrode plate and battery
CN118553892A
Lithium-sodium composite lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN118811873A